Vocabulary in use intermediate - Redman, Stuart (Cambrige University Press, 1999)
Vocabulary in Use Intermediate helps students who have mastered basic words and phrases to consolidate and expand their knowledge of English vocabulary. The book contains 100 lessons covering approximately 2,500 vocabulary items. Ideal for self-study, its easy-to-use format presents content or grammar-based vocabulary on the left-hand page and innovative practice activities on the right-hand page. An edition without answers, suitable for classroom use, is available.